Peningkatan Employee Performance Berbasis Transformasional Leadership, Organization Citizen Behavior Dan Work Motivation PT PLN (Persero) Unit Pelaksana Pelayanan Pelanggan Balikpapan - Nirwan Komarudin (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2024)
Additional PT customers. PLN (Persero) Balikpapan Customer Service Implementation Unit experiences a decline every year. The decline in customers also shows an indication of a decline in employee performance. Factors that influence employee performance include transformational leadership, Organizational citizenship behavior (OCB), and work motivation. This research aims to: 1)Test and analyze the influence of transformational leadership on OCB; 2)Test and analyze the influence of transformational leadership on work motivation; 3)Test and analyze the influence of OCB on employee performance; 4)Test and analyze the influence of transformational leadership on employee performance; 5)Test and analyze the influence of work motivation on employee performance at PT PLN (Persero) Balikpapan Customer Service Implementation Unit. This research uses a quantitative approach, where data collection is carried out by distributing questionnaires (primary data) to active employees who work at PT PLN (Persero) Balikpapan Customer Service Implementation Unit. The primary data source comes from the results of the questionnaire filled in by respondents. Data analysis using smartPLS. Instrument testing uses validity and reliability tests. The research results show that 1)Transformational leadership has a significant positive effect on organizational citizenship behavior. 2)Transformational leadership has a significant positive effect on work motivation. 3)Organizational citizenship behavior has a significant positive effect on employee performance. 4)Transformational leadership has a significant positive effect on employee performance. 5)Work motivation has a significant positive effect on employee performance.